A facile method for preparing CNT-grafted carbon fibers and improved tensile strength of their composites. (February 2015) - Lee, Geunsung; Ko, Kwang Duk; Yu, Young Chang; Lee, Jinyong; Yu, Woong-Ryeol; Youk, Ji Ho
Abstract: Carbon nanotube (CNT)-grafted carbon fibers (CFs) have emerged as new reinforcements for improving the mechanical properties of CF-reinforced composites but such enhancement in macroscale composites has not been realized. This paper reports a facile method for preparing CNT-grafted CFs and improving the tensile strength of their composites. A CNT/polyacrylonitrile solution was sprayed onto the surface of the CF woven fabrics, and the CNTs were grafted by a thermal treatment at 300 °C. CNT-grafted CF composites were fabricated using the CNT-grafted CF woven fabrics using a vacuum-assisted resin transfer molding process with epoxy resin. The CNT-grafted CF composite exhibited 22% enhancement in the tensile strength compared to that of the pristine CF composite. Fracture surfaces of the CNT-grafted CF composites showed that the grafted CNTs obstructed the propagation of micro-cracks and micro-delamination around the CFs and also yarn boundaries, resulting in improved tensile strength of CNT-grafted CF composites.